2020
DOI: 10.25259/ijmio_13_2020
|View full text |Cite
|
Sign up to set email alerts
|

Why we should rely only on molecular tests based on Indian data

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution-Non Commercial-Share Alike 4.0 License, which allows others to remix, tweak, and build upon the work non-commercially, as long as the author is credited and the new creations are licensed under the identical terms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In India, the regulatory authorities (DCGI and ICMR) have clearly recommended that such testing should not be used in clinical practice unless validated amongst Indian patients. 55 56 Wang et al 57 showed that OncotypeDx is not cost-effective even in low-risk patients. The cost-effectiveness analyses (CEAs) ignoring clinicopathological information are problematic, not only because they depart from clinical practice but also because they result in inappropriate conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…In India, the regulatory authorities (DCGI and ICMR) have clearly recommended that such testing should not be used in clinical practice unless validated amongst Indian patients. 55 56 Wang et al 57 showed that OncotypeDx is not cost-effective even in low-risk patients. The cost-effectiveness analyses (CEAs) ignoring clinicopathological information are problematic, not only because they depart from clinical practice but also because they result in inappropriate conclusions.…”
Section: Discussionmentioning
confidence: 99%